Electrocardiographic Changes in Child Athletes - Akpınar Gözetici, Melis; Bostan Kantarcı, Aysenur; Türkmenoğlu, Yelda; Dursun, Hasan; İrdem, Ahmet (Cerrahpaşa Medical Journal, 2022)
Objective: This study aimed to investigate changes in cardiac function in child athletes. Methods: Electrocardiogram and echocardiograms of 136 child athletes were included. Heart rate, rhythm, electrical axis, P wave duration, PR interval, QRS interval, sum of V1-S + V5-R wave amplitude, V1-S/V5-R amplitude ratio, sum of V1-S + V6-R wave amplitude, V1-S/V6-R amplitude ratio, QT and QTc intervals, QT and QTc dispersions, JT and JTc intervals T peak-end (Tp-e) interval, presence of early repolarization pattern, left ventricular internal dimension in diastole and systole, and fractional shortening were recorded. The data were compared to the control group of 90. Results: In the child athletes, the mean QRS amplitude, QT interval, QTd, JT interval, Tp-e, left ventricular internal dimension in diastole and systole were found to be increased and heart rate was found to be decreased compared to the control group. The differences were statistically significant. In children who had exercised more than 1000 hours, mean heart rate was found to be decreased, PR interval, QRS interval, V1-S + V5-R wave amplitude, and left ventricular internal dimension in systole were found to be increased compared to the children who had exercised less than 1000 hours. The differences were statistically significant. Conclusion: Ventricular repolarization got affected in child athletes, and the duration of exercise determined the degree of cardiac change. Cite this article as: Akpınar Gözetici M, Bostan Kantarcı A, Türkmenoğlu Y, Dursun H, İrdem A. Electrocardiographic changes in child athletes. Cerrahpaşa Med J. 2022;46(1):71-74.